Computational modeling of malignant ascites reveals CCL5–SDC4 interaction in the immune microenvironment of ovarian cancer. Issue 5 (15th March 2021) - Kim, Soochi; Han, Youngjin; Kim, Se Ik; Lee, Juwon; Jo, HyunA; Wang, Wenyu; Cho, Untack; Park, Woong‐Yang; Rando, Thomas A.; Dhanasekaran, Danny N.; Song, Yong Sang
Abstract: Fluid accumulation in the abdominal cavity is commonly found in advanced‐stage ovarian cancer patients, which creates a specialized tumor microenvironment for cancer progression. Using single‐cell RNA sequencing (scRNA‐seq) of ascites cells from five patients with ovarian cancer, we identified seven cell types, including heterogeneous macrophages and ovarian cancer cells. We resolved a distinct polarization state of macrophages by MacSpectrum analysis and observed subtype‐specific enrichment of pathways associated with their functions. The communication between immune and cancer cells was predicted through a putative ligand–receptor pair analysis using NicheNet. We found that CCL5, a chemotactic ligand, is enriched in immune cells (T cells and NK cells) and mediates ovarian cancer cell survival in the ascites, possibly through SDC4. Moreover, SDC4 expression correlated with poor overall survival in ovarian cancer patients. Our study highlights the potential role of T cells and NK cells in long‐term survival patients with ovarian cancer, indicating SDC4 as a potential prognostic marker in ovarian cancer patients.